Assessment of Land Use and Land Cover Changes in Afi River Forest Reserve Cross River State, Nigeria - C. I. Duru; U. D. Chima; C. Fredrick (Journal of Agroforestry and Environment)
Forest conversion remains a pressing concern for the global environmental community. This study evaluated the impact of land use and land cover (LULC) changes on selected ecosystem components in the Afi River Forest Reserve, Cross River State, Nigeria. Spatial and temporal changes over a 30-year period (1992 to 2022) were evaluated using Landsat-4 Thematic Mapper (TM) for the 1992 images and Landsat-7 Enhanced Thematic Mapper (ETM) images for 2002 and 2022. A supervised classification method was employed to classify and map LULC types and future changes up to 2052 predicted. Six distinct land use types-dense vegetation, farmland/sparse vegetation, built-up area, bare land, rock, and water bodies were identified. A significant decline in dense vegetation from 312.14 km² in 1992 to 271.28 km² in 2022 was observed while farmland, built-up areas, and bare land increased. The decline in dense vegetation highlights the pressures from agricultural expansion, urbanization, and other anthropogenic activities. A further decline in dense vegetation to 220.32 km² by 2052 and further expansions in the areas covered by farmland, water bodies, built-up areas, and bare land, were predicted. The observed trends highlight the urgent need for immediate action to combat environmental degradation in the Afi River Forest Reserve. Prioritizing sustainable land use practices, such as agroforestry and sustainable agriculture, is essential to alleviate agricultural pressures. Strengthening community-based forest management programs to foster local participation and commitment to conservation efforts. Furthermore, continuous monitoring of LULC changes is vital for informing adaptive management strategies and implementing effective policy interventions.